Efficiency of Lemna minor and Eichhornia crassipes in an artificial aerobic pond prototype for removing thermotolerant coliforms from surface waters of the Huaura River, Peru. - Maguiña-Cenas, Manuel Jesus (2025)
Thermotolerant coliform contamination in the surface waters of the Huaura River poses a significant risk to public health and natural ecosystems, both aquatic and terrestrial, highlighting the urgent need to implement sustainable treatments. The objective of this study was to evaluate the phytoremediation efficiency of the macrophytes Lemna minor and Eichhornia crassipes for the removal of thermotolerant coliforms from the surface waters of the Huaura River. Six prototypes of artificial aerobic lagoons with a retention time of 20 days were implemented, distributed in three experimental units for each species evaluated: Lemna minor (T1) and Eichhornia crassipes (T2). The initial biomass was 40 g/L in both macrophytes, including a control prototype without vegetation cover (T0). The results showed that both treatments with macrophytes achieved statistically significant removal (P < 0.05). L. minor (T1) showed high removal efficiency (98.73 ± 0.15%). E. crassipes (T2) achieved an efficiency of 97.57 ± 2.91%, although starting from heterogeneous initial contamination conditions. The physicochemical parameters in the macrophyte treatments showed pH alkalization and an increase in electrical conductivity in both treatments, the latter being more pronounced with E. crassipes (T2). Therefore, it is concluded that both macrophyte species used in the prototypes for the treatment of contaminated water from the Huaura River are effective, with L. minor (T1) showing greater efficiency and being the most predictable species for the scaling up of phytoremediation systems for surface water.